Mechanism-anchored ecological risk assessment of phthalates in coastal waters: Bridging environmental fate and molecular toxicity via an AOP framework - Shao-Yang Bu; Li-Ju Tan; Yan-Shan Chen; Kun Lin; Jiang-Tao Wang (Marine Pollution Bulletin, 2026)

Defect-engineered BiOBr/g-C3N4 heterojunction anchored on Ulva prolifera biochar for enhance photocdatalytic degradation of tetracycline - Yingchao Li; Yanan Tan; Yefei Qu; Yunyi Chen; Minggang Zheng; Zuhao Zhu; Pengcheng Zhang; Peng Ju (Environmental Research, 2026)

Damage response and postnatal compensatory repair in the male offspring mouse reproductive system following gestational cadmium exposure - Jiaqiao Zhu; Ankai Tan; Yixuan Lu; Huiling Guo; Lina Ye; Zhutao Huang; Yonggang Ma; Hui Zou; Junwei Li; Huiming Ju; Zongping Liu (Toxicology and Applied Pharmacology, 2026)

Spectral and structural analysis of a new lactone metabolite isolated from a mangrove endophytic fungus - Meijing Tan; Shichao Ju; Fan He; Wenjun Li; Youquan Wei; Rui Pi; Xishan Huang; Yanjun Zhang (Natural Product Research, 2026)

Guxiaspergiltones A-J: Furanone-type polyketides with anti-inflammatory activities from the mangrove endophytic fungus Aspergillus sp. GXNUW29 - Fan He; Furong Wu; Meijing Tan; Xianglong Bo; Shichao Ju; Wenjun Li; Youquan Wei; Jiao Wu; Xishan Huang (Phytochemistry, 2026)

Chemical-free lithium separation from high-salinity brines using model-informed and machine learning-optimized multi-column zwitterionic chromatography - Jun Woo Park; Daniel Li; Marcus Condarcure; Zbyslaw Owczarczyk; Ariel R. Lepard; Louis A. Chirban; Joel Miscall; Eric C.D. Tan; Ju Weon Lee; Ki Bong Lee; Hoon Choi (Journal of Cleaner Production, 2026)

A new diphenyl ether with insecticidal activity from the mangrove endophytic fungus Aspergillus sp. GXNU-DY2-12 - Meijing Tan; Shichao Ju; Fan He; Wenjun Li; Youquan Wei; Weifeng Xu; Ruiyun Yang; Xishan Huang (Natural Product Research, 2026)

Post-thinning recovery time and litter quality co-regulate litter decomposition in mixed oak-pine forests - Shuiqiang Yu; Shizhou Ju; Rui Tan; Xiangfu Wang; Zi’ao Liang; Yu Li; Yuanhui Li; Weifeng Wang (Forest Ecology and Management, 2026)

A fast powerful X-ray transient from possible tidal disruption of a white dwarf - Dongyue Li; Wenda Zhang; Jun Yang; Jin-Hong Chen; Weimin Yuan; Huaqing Cheng; Fan Xu; Xinwen Shu; Rong-Feng Shen; Ning Jiang; Jiazheng Zhu; Chang Zhou; et al. (Science Bulletin, 2026)

Two new polyketone derivatives from the mangrove endophytic fungus Aspergillus sp. GXNU TH4b - Shichao Ju; Xianglong Bo; Furong Wu; Meijing Tan; Zisuo Song; Fan He; Wenjun Li; Youquan Wei; Weifeng Xu; Ruiyun Yang; Xishan Huang (Natural Product Research, 2026)

N-propyl gallate treatment maintains postharvest quality and doubles the shelf life of Akebia trifoliata fruit - Xiaoxiao Yi; Ju Guan; Jie Li; Shengfu Zhong; Chen Chen; Feiquan Tan; Jinliang Shen; Huabai Han; Zongxiang Tang; Peigao Luo (Food Control, 2025)

Constructing Ni2P/CoP heterojunction with stable built-in electric field to boost overall water splitting at industrial current density - Tian Lin; Huimin Yang; Jianguo Dong; Chunmei Ni; Xuena Gao; Jing Li; Ju Wang; Xiaoyan He; Wenyi Tan; Ligang Feng; Zhao Li (Fuel, 2025)

Cytotoxic metabolites from the mangrove endophytic fungus Aspergillus sp. GXNU QG1a - Xianglong Bo; Yufei Zhao; Feng Qin; Furong Wu; Meijing Tan; Shichao Ju; Zishuo Song; Wenjun Li; Fan He; Youquan Wei; Hua Xu; Xishan Huang (Natural Product Research, 2025)

Monitoring of genetically modified crops in food products in Singapore - Yanwen Wang; Kung Ju Lin; Emily Huey Shyan Teo; Yong Quan Tan; Yuansheng Wu; Kern Rei Chng; Joanne Sheot Harn Chan; Li Kiang Tan (Food Control, 2025)

A new sulphur-containing metabolite from a mangrove endophytic fungus Aspergillus sp. GXNU-MA - Furong Wu; Wenxiu Zhang; Xianglong Bo; Qin Feng; Meijing Tan; Shichao Ju; Zishuo Song; Jun Li; Xishan Huang (Natural Product Research, 2025)

Highly reliable anti-reflection radiative cooling glass applicable to thermal management of solar cells - Qihao Dai; Peng Xiang; Bowen Li; Xiongbo Yang; Zheng Guo; Hong Zhang; Qi Luo; Chenyu Ju; Hongxing Weng; Yiming Liu; Xinyu Tan (Chemical Engineering Journal, 2024)

Effects of chronic low-level lead (Pb) exposure on cognitive function and hippocampal neuronal ferroptosis: An integrative approach using bioinformatics analysis, machine learning, and experimental validation - Yingsi Cao; Wenjing Zhao; Yanqi Zhong; Xiaofan Jiang; Huiya Mei; Yuanjin Chang; Dongqin Wu; JianRui Dou; Emely Vasquez; Xian Shi; Jiatao Yang; Zhongtang Jia; et al. (Science of The Total Environment, 2024)

Remediation of atrazine-contaminated soil in a fluidized-bed DBD plasma reactor - Nan Jiang; Ying Qu; Jinwei Zhu; Hongchang Wang; Ju Li; Yun Shu; Yutao Cui; Yuling Tan; Bangfa Peng; Jie Li (Chemical Engineering Journal, 2023)

A multispectral method for retrieving overlapping cloud top heights from passive radiometers - Shiwen Teng; Chao Liu; Zhonghui Tan; Jiming Li; Na Xu; Xiuqing Hu; Peng Zhang; Wei Yan; Byung-Ju Sohn (Remote Sensing of Environment, 2023)

Optimal design of inhomogeneous semi-transparent photovoltaic windows based on daylight performance and visual characters - Xinyi Li; Jinqing Peng; Yutong Tan; Yingdong He; Bojia Li; Xiaolei Ju; Jie Ji; Song Zhang; Nianping Li; Youming Chen (Energy and Buildings, 2023)

Preparation of alumina/silica/exfoliated graphite nanoplatelets composite aerogels and its application as supporting material for erythritol based form-stable phase change materials - Yu-Hao Ning; Ye Tan; Chuan-Huang Lin; Qi Li; Lin-Ping Yu; Zhong Cao; Li-Xian Sun; Chuan-Chang Li; Ju-Lan Zeng (Chemical Engineering Journal, 2023)

Biogenetic peloidal micrites within coral skeletons cause geochemical anomalies in reef limestones, Zhongsha Atoll, South China Sea - Hong-Qiang Yang; Xi-Yang Zhang; Yue Li; Qi Shi; Shi-Chen Tao; Xi-Nan Mu; Ming-Zhuang Wang; Xiao-Ju Liu; Fei Tan; Sheng-Nan Zhou; Guan Wang (Palaeogeography, Palaeoclimatology, Palaeoecology, 2023)

Two new organic acids from Portulaca oleracea L. and their anti-inflammatory and anticholinesterase activities - Peishan Liu; Lingling Wang; Huanfeng Li; Lishuang Tan; Xixiang Ying; Baozhao Ju (Natural Product Research, 2022)

Prediction of disability-free survival in healthy older people - Johannes Tobias Neumann; Le T. P. Thao; Anne M. Murray; Emily Callander; Prudence R. Carr; Mark R. Nelson; Rory Wolfe; Robyn L. Woods; Christopher M. Reid; Raj C. Shah; Anne B. Newman; Jeff D. Williamson; et al. (GeroScience, 2022)
Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability or death. Selection of potential predictors from amongst 25 biomedical, psychosocial and lifestyle variables including recognized geriatric risk factors, utilizing a machine-learning approach. Separate models were developed for men and women. The selected predictors were evaluated in a multivariable Cox proportional hazards model and validated internally by bootstrapping. We included 19,114 Australian and US participants aged ≥65 years (median 74 years, IQR 71.6–77.7). Common predictors of a worse prognosis in both sexes included higher age, lower Modified Mini-Mental State Examination score, lower gait speed, lower grip strength and abnormal (low or elevated) body mass index. Additional risk factors for men included current smoking, and abnormal eGFR. In women, diabetes and depression were additional predictors. The biased-corrected areas under the receiver operating characteristic curves for the final prognostic models at 5 years were 0.72 for men and 0.75 for women. Final models showed good calibration between the observed and predicted risks. We developed a prediction model in which age, cognitive function and gait speed were the strongest predictors of disability-free survival in healthy older people. Trial registration Clinicaltrials.gov (NCT01038583)

Phenolic glycosides from Sanguisorba officinalis and their anti-inflammatory effects - Jin-feng Chen; Lu Tan; Feng Ju; Qi-xuan Kuang; Tian-long Yang; Fang Deng; Yu-cheng Gu; Li-shi Jiang; Yun Deng; Da-le Guo (Natural Product Research, 2022)

Enhanced treatment of shale gas fracturing waste fluid through plant-microbial synergism - Bo Shao; Xu Tan; Ju-Long Li; Mei He; Lei Tian; Wen-Jie Chen; Yan Lin (Environmental Science and Pollution Research, 2021)

CSF Brain-Reactive Autoantibodies are Elevated in Patients with Viral Encephalitis - Zhong-Yuan Yu; Jian-Hong Wang; Wei-Wei Li; Ye-Ran Wang; Noralyn B. Mañucat-Tan; Jun Wang; Ju Wang; Gao-Yu Cui; Jie-Xiang Pan; Shui-Xian Zhang; Zu-Juan Liu; Liang Tan; et al. (Neuroscience Bulletin, 2020)

Advances in Urban Meteorological Research in China - Shiguang Miao; Weimei Jiang; Ping Liang; Hongnian Liu; Xuemei Wang; Jianguo Tan; Ning Zhang; Ju Li; Wupeng Du; Lin Pei (Journal of Meteorological Research, 2020)

Theoretical study of the mechanism of the manganese catalase KatB - Xi-Xi Yang; Qiu-Yun Mao; Xiao-Ting An; Xi-Chen Li; Per E. M. Siegbahn; Guang-Ju Chen; Hong-Wei Tan (JBIC Journal of Biological Inorganic Chemistry, 2019)

Construction of a small-caliber tissue-engineered blood vessel using icariin-loaded β-cyclodextrin sulfate for in situ anticoagulation and endothelialization - Jingyuan Yang; Keyu Wei; Yeqin Wang; Yanzhao Li; Ning Ding; Da Huo; Tianran Wang; Guanyuan Yang; Mingcan Yang; Tan Ju; Weng Zeng; Chuhong Zhu (Science China Life Sciences, 2018)

Error inhomogeneity in the computation of spherical mean displacement - Xuezhong Wang; Banghui Hu; Hong Huang; Ju Wang; Gang Zeng; Yanke Tan; Li Zou (Journal of Meteorological Research, 2017)

New Labdane diterpenes from Hedychium yunnanense with cytotoxicity and inhibitory effects on nitric oxide production - Yu-Peng Li; Si-Meng Zhao; Jun-Ju Xu; Guang-Zhi Zeng; Yan Li; Ning-Hua Tan; Ye Yang (Natural Product Research, 2016)

Chronic effects of ketamine on gene expression changes in neurotransmitter receptors and regulators-A PCR-array study - Sijie Tan; Ju Zou; Meixiang Li; David T. Yew (Molecular & Cellular Toxicology, 2015)

Partial defoliation and runner removal affect runnering, fruiting, leaf photosynthesis and root growth in ‘Toyonoka’ strawberries for subtropical winter production - Chia-Bin Lyu; Wen-Ju Yang; Kuo-Tan Li (Horticulture, Environment, and Biotechnology, 2014)

Protective effect of vitexin compound B-1 against hypoxia/reoxygenation-induced injury in differentiated PC12 cells via NADPH oxidase inhibition - Zhong-Bao Yang; Bin Tan; Ting-Bo Li; Zheng Lou; Jun-Lin Jiang; Ying-Jun Zhou; Jie Yang; Xiu-Ju Luo; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2014)

Differential responses to short-term salinity stress of heat-tolerant cherry tomato cultivars grown at high temperatures - Fang-Yi Liu; Kuo-Tan Li; Wen-Ju Yang (Horticulture, Environment, and Biotechnology, 2014)

Genome-wide association study identified novel genetic variant on SLC45A3 gene associated with serum levels prostate-specific antigen (PSA) in a Chinese population - Jielin Sun; Sha Tao; Yong Gao; Tao Peng; Aihua Tan; Haiying Zhang; Xiaobo Yang; Xue Qin; Yanling Hu; Junjie Feng; Seong-Tae Kim; Xiaoling Lin; et al. (Human Genetics, 2013)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Analysis of the antibodies anti-Toxoplasma gondii by ELISA based on two diagnostic antigens: rSAG1 and rBAG1 - Min Liu; Tao Wang; Hua Li; Ju-Ying Li; Han Zhong; Chang-Zan Tan; De-Cheng Huang; Liang Zhao; Xiao-Guang Chen; Zhao-Rong Lun (Acta Parasitologica, 2011)
Schizophrenia is a serious neuropsychiatric disease of uncertain etiology. Previous studies have demonstrated that antibodies to Toxoplasma gondii infection are associated with an increased risk of schizophrenia. The objective of this study was to analyze anti-T. gondii antibodies in 477 Chinese schizophrenia patients using an enzyme-linked immunosorbent assay (ELISA) based on recombinant surface antigen 1 (rSAG1), recombinant bradyzoite antigen 1 (rBAG1) and the soluble tachyzoite antigens (STAg) of T. gondii RH strain. Results showed that among the sero-positives (IgG and/or IgM) for T. gondii infection examined in schizophrenia patients, sero-positive samples for rSAG1, rBAG1 and STAg were 20.5% (98/477), 20.5% (98/477) and 23.5% (112/477) respectively, while compared to 210 blood donors, sero-positive (IgG and/or IgM) samples for these antigens (rSAG1, rBAG1 and STAg) were only 5.7% (12/210), 6.2% (13/210) and 5.7% (12/210), respectively. Furthermore, when IgG antibody reaction in the schizophrenia sera was compared with the rBAG1 and rSAG1, results demonstrated that beside the cases which can be detected by both rSAG1 and rBAG1, some sero-positive for T. gondii in schizophrenia sera can only be detected either by rSAG1 or rBAG1. This phenomenon was also observed in the detection of IgM with rSAG1 and rBAG1. 5.9% (28/477) of cases of schizophrenia which are positive for IgG or IgM by rSAG1 are negative for STAg, while 9.2% (44/477) of the schizophrenia cases which are positive for IgG or IgM by rBAG1 are negative for STAg. Although STAg can also be used to diagnose T. gondii infection from schizophrenia patients, it may not actually indicate the infection as some positive samples may be mistakenly considered to be negative. In conclusion, our results demonstrate that the sero-positive rate for T. gondii in the Chinese schizophrenia patients was higher than blood donors. More importantly, our results provide evidence that the combination of rSAG1 and rBAG1 antigens in the diagnosis of T. gondii infection could closely reflect the actual infection of this parasite in schizophrenia patients.